2020
DOI: 10.1051/ro/2018099
|View full text |Cite
|
Sign up to set email alerts
|

Replenishment of imperfect items in an EOQ inventory model with partial backordering

Abstract: This paper deals with an inventory model in which a percent of the items in the lot is imperfect. The supplier is far from the buyer. After the reception of the order, immediately the products are inspected and imperfect items are identified. Due to the fact that supplier is located at long distance and the demand is needed to cover, the imperfect items are replenished by perfect ones from a local supplier at higher cost. In addition, the imperfect items are withdrawn and sold at a salvaged price as second-deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 33 publications
(45 reference statements)
0
4
0
Order By: Relevance
“…Pervin et al [19] initiated an inventory model with shortage under time-dependent demand and stochastic deterioration. Taleizadeh et al [33] discussed the replenishment of imperfect items in an EOQ inventory model with partial back-ordering.…”
Section: Motivation and Review On Researchmentioning
confidence: 99%
“…Pervin et al [19] initiated an inventory model with shortage under time-dependent demand and stochastic deterioration. Taleizadeh et al [33] discussed the replenishment of imperfect items in an EOQ inventory model with partial back-ordering.…”
Section: Motivation and Review On Researchmentioning
confidence: 99%
“…Khakzad and Gholamian [51] investigated the effect of inspection time on the deterioration rate; they showed the convexity of the model and illustrated the uniqueness of the solution. Taleizadeh et al [52] revealed an EOQ inventory model with imperfect items and partial backordering. They assumed a percent of the products in a lot is imperfect and the imperfect items are replenished by perfect ones at a higher cost.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They also formulated the optimal lot size, while the reworkable items are kept in the warehouse. Further related research is available in Taleizadeh et al (2016), Aslani et al (2017) and Taleizadeh et al (2018).…”
Section: Introductionmentioning
confidence: 99%